Razprte Podobe - Széttart Képek - Disclosed Images : The Young Slovene Art of the Seventies and the Eighties. (Ljubljana : Moderna Galerija, 1989)
Barsi, Joze ; Gorenec, Bojan ; Hocevar, Zoran ; Kapus, Sergej ; Lenardic, Zmago ; Pocivavsek, Matjaz ; Pogacar, Tadej ; Potrc, Marjetica ; Duba ; Susnik, tugo ; Vodopivec, Lujo ; Zidar, Dusan ; etc.
Disclosed Images : The Young Slovene Art of the Seventies and the Eighties, Moderna Galerija, Ljubljana, Szombathelyi Képtár, Szombathely, 09. - 10.1989 ; Ernst Museum, Budapest, 01. - 02.1990
Engels-Sloveens
kunstcatalogus
Keywords: Slovenië